SO‘FIYLIK FALSAFASI VA UNING NUTQ MADANIYATIDA LINGVISTIK IFODASI ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This research examines how the philosophy of Sufism is expressed through linguistic and communicative means in Eastern and Western literary texts. The main focus of the study is on language and communication tools, including metaphoric expressions, phraseological units, and quotations, which are analyzed to understand how philosophical ideas, moral values, and spiritual experiences are effectively conveyed to the audience. Additionally, the study explores the role of Sufi philosophical expressions in speech culture and communicative processes. This study contributes to the fields of Eastern and Western literature, linguistics, stylistics, and cultural studies, offering new insights into the relationship between speech culture and linguistic expression of Sufi philosophical ideas